Differences in Symptoms of Primary Dysmenorrhea - Sandra Alejandra Fernández Macedo; Julio Jimenez Agüero; Graciela Bernal Salas; Sonia Benita Fernandez Tapia; Esperanza Cueva Rossel (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
The objective of the study was to establish semiological differences associated with primary dysmenorrhea in female university students from a University in Peru. Dysmenorrhea is a condition that manifests itself before, during and after menstruation and is accompanied by very intense pelvic pain. Women experience menstrual cramps, which decreases their quality of life. Those who begin their menstrual cycles with these symptoms assume that it is normal and that specialized medical assistance is not necessary. Medical professionals have established general practice guidelines on clinical disorders of the menstrual cycle, However, there are no specific recommendations that effectively support the timely diagnosis and treatment of primary dysmenorrhea. The particularity of our research is that the symptoms they can vary depending on the altitude of 3870 meters above sea level, so it is necessary to continue with experimental and comparative research.